Analisis Perdagangan Bilateral Indonesia Indonesia dengan Malaysia Periode 2003-2012 - Maulana, Iskandar; Putro, Tri Sukirno; ', Darmayuda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine (bilateral) development and comparison of trade between the two countries, Indonesia and Malaysia for the period 2003 to 2012 As this study shows the shape of trade, and the indicators that affect trade between Indonesia and Malaysia. The data used are secondary data obtained from the BPS (Central Bureau of Statistics) and the World "series for 10 years. "Variable used, among other things, the value of exports and imports, the price level and GDP.Methods for quantitative data analysis and descriptive data analysis. Indonesia bilateral trade with Malaysia calculations using the formula expor-import price index is likely to rise sharply, particularly in terms of export and import small. Taken together, the independent variable is the dependent variable to explain export function. In terms of the commercial value of Indonesia and Malaysia in 2003-2012, an average exchange rate of Indonesian trade showed 100 percent, this means that the state of Indonesia and Malaysia are still mutually beneficial bilateral trade import and export business midst of the economic turmoilKeywords: Bilateral, exchange rate, index of export and import of Indonesia.